2021
DOI: 10.36246/ul.2021.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Kölcsönösen átjárható városi, – és elővárosi vasúti rendszerek globális forgalmi hatásainak komplex vizsgálata

Abstract: Budapest elővárosi és a városi vasúti közlekedési rendszere több eltérő szolgáltatási színvonalú és műszaki paraméterű, egymástól elszigetelt vasúti rendszert tartalmaz, amelyek integrálása elengedhetetlen a mai modern kor átszállásmentes utazási igényeinek való megfeleléshez, valamint a főváros fokozatosan növekvő agglomerációs forgalmának kiszolgálásához. A cikkben bemutatásra kerül az M3-as metró és a Lajosmizsei vasútvonal átjárhatóságának komplex vizsgálata során alkalmazott forgalmi modellezési eljárás. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…According to the mining data [18], the Dezső Rezső Valley is placed almost perpendicularly to the dip of the iron ore body, which continues in the southern direction from the valley [18] (p. 189) (Figure 2) beneath the plowland beyond a further 200 m. Occasionally, spring or autumn plowing delivers blocks from the lower soil. In this way, we collected these samples in the field (Figure 6).…”
Section: Dezső Rezső Valley Outcropsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the mining data [18], the Dezső Rezső Valley is placed almost perpendicularly to the dip of the iron ore body, which continues in the southern direction from the valley [18] (p. 189) (Figure 2) beneath the plowland beyond a further 200 m. Occasionally, spring or autumn plowing delivers blocks from the lower soil. In this way, we collected these samples in the field (Figure 6).…”
Section: Dezső Rezső Valley Outcropsmentioning
confidence: 99%
“…The tiny depositional iron ore body at Zengővárkony (Mecsek Mountains, South Hungary) was discovered by Mr. Rezső Dezső, a private entrepreneur who made magnetic inclination measures in the 1930s. After World War II, the Hungarian State opened an ore mine that produced approximately 24,850 tons of iron ore between 1954 and 1956 [18]. Scientific research has also started [19], and a rich microfossil content was reported by [20].…”
Section: Introductionmentioning
confidence: 99%
“…According to the mining data (Molnár 1961) the Dezső Rezső Valley is placed almost perpendicular to the dipping of the iron ore body that continues in southern direction from the valley (Molnár 1961 p.…”
Section: Hydrothermal Deposits (Figs 3-4)mentioning
confidence: 99%
“…His mining licence was confiscated and the Hungarian State opened the ore mine in the 1950s. Parallel to the mining activity, that produced some 24,850 tons of iron-ore between 1954 and 1956 (Molnár 1961) the scientific research also has started (Sztrókay 1952). Rich microfossil content from the cover of the ore body was reported by Pantó et al (1955).…”
Section: Introductionmentioning
confidence: 99%